Effectiveness of Toothpaste containing Pyrophosphate and Papain to Inhibit Calculus Formation in patient using Fixed Orthodontic Appliance - I Gusti Aju Wahju Ardani, - (A and V Publications, 2019)
Patients using fixed orthodontic appliance are more susceptible to calculus formation than patient without orthodontic treatment. Pyrophosphate and papain toothpaste can be used to reduce dental plaque and calculus accumulation. The aim of this study was to analyze the differences in the calcium level and phosphate level in saliva, also saliva pH in patient’s after treated with toothpaste containing pyrophosphate and papain. This study was true experimental study with pre-test and post-test controls group design with random sampling. Sample size was (n=20). Sample was 17-22 years old male or female patient using fixed orthodontic appliance. Sample divided into two groups: control group treated with placebo toothpaste and treatment group treated with toothpaste containing pyrophosphate and papain with blind method. Patients were instructed to brush their tooth twice a day daily. 3 ml unstimulated saliva was collected on the Day 1, 3, and 5. Spectrophotometer Atom Absorbance (SAA) was used to measure calcium level and phosphate level in saliva, while saliva pH measurement using pH meters. Treatment group showed lowest mean (SD) calcium level [1.12(0.29]. Calcium level in treatment group between groups (p<0.05) was significantly different. Saliva pH was insignificantly different between groups (p>0.05). Treatment group showed lowest phosphate level in Day 5. Phosphate level in treatment group between groups (p<0.05) was significantly different. Toothpastes containing pyrophosphate and papain decreased calcium levels, phosphate levels effectively and maintaining normal salivary pH to inhibit calculus formation in patients using fixed orthodontic appliance.